2019
DOI: 10.1590/2317-1545v41n1191888
|View full text |Cite
|
Sign up to set email alerts
|

Tomato seed image analysis during the maturation

Abstract: The seed physiological potential has been directly related to normal formation process under morphological, structural and functional point of view. The objective of this study was to evaluate the internal morphology of ‘BRS Nagai’ tomato hybrid seeds at different stages of development and maturation, through the X-ray image analysis and relate the results with the seed germination and vigor. Seeds were extracted from fruits harvested at 30, 40, 50, 60 and 70 days after pollination (DAP). Subsequently, seeds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…The software ImageJ, used in the present work, possesses additional advantages since it is free of charge and offers a vast set of tools for image analysis (Schneider, Rasband, & Eliceiri, ). Some recent research has also shown the efficiency of ImageJ in processing seed radiographs (Abud et al., ; Borges et al., ; de Medeiros et al., , ; Leão‐Araújo et al., ; Prado‐Alves, de Von Pinho, dos Santos, Prado‐Alves, & de Carvalho, ). Nevertheless, more studies in this field remain necessary, especially for seeds of small size, extracted from fruits at different maturation stages, the case of several crop species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The software ImageJ, used in the present work, possesses additional advantages since it is free of charge and offers a vast set of tools for image analysis (Schneider, Rasband, & Eliceiri, ). Some recent research has also shown the efficiency of ImageJ in processing seed radiographs (Abud et al., ; Borges et al., ; de Medeiros et al., , ; Leão‐Araújo et al., ; Prado‐Alves, de Von Pinho, dos Santos, Prado‐Alves, & de Carvalho, ). Nevertheless, more studies in this field remain necessary, especially for seeds of small size, extracted from fruits at different maturation stages, the case of several crop species.…”
Section: Discussionmentioning
confidence: 99%
“…The x‐ray testing, also regarded as an optical technology, places among the most used ones for visualization of internal morphology of seeds. Recent research in the seed area showed the use of radiographic images for diverse purposes, such as detecting embryonic malformations and physical damages, as well as for monitoring seed filling, maturation, and overall quality (Abud, Cicero, & Gomes, ; Medeiros et al., , ; Borges et al., ; Leão‐Araújo, Gomes‐Junior, da Silva, Peixoto, & de Souza, ). However, the analysis of the radiograph visually is subjective, leading to errors, laborious and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…As observed by the automated physical analysis, the lots with higher values of tissue density, fi lling, and solidity, presented higher germination and vigor. Similarly, the direct relation between tissue density and / or fi lling with the physiological quality of seeds has already been observed both in forest species such as L. leucocephala (Medeiros et al, 2018), M. polymorphum (Faria et al, 2019) and M. oleifera (Noronha et al, 2019), and in other agricultural species such as tomato ( Borges et al, 2019) and Jatropha curcas (Medeiros et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
“…Several authors pointed out that the evaluation of aspects such as the internal cavity occupied by the embryo, the presence of mechanical damages, stains that indicate tissue deterioration or seed malformations is necessary in studies with X-rays in seeds (Borges et al, 2019;Gomes-Junior et al, 2013). However, according to , all these characteristics are in a way represented by the relative density, since seeds deteriorated or with less filling show lower gray levels in the radiographic image.…”
Section: Resultsmentioning
confidence: 99%
“…With the filling variable, which represents the percentage of area of the seed effectively filled by high density material, we noticed that the lowest observed averages value was 93.6%, which indicates high uniformity of embryonic filling perceived in the seed lots studied. Borges et al (2019) also used the filling variable to quantify the empty seed area of tomato, and observed a close relationship between seed empty space and its physiological quality.…”
Section: Resultsmentioning
confidence: 99%